Nurturing professionalism and humanism in the 21st century medical professional - Rajput, Vijay (Research and Humanities in Medical Education, 2014)
There is a need to redefine physician excellence through promoting professionalism with humanism to meet the needs of a diverse generational and cultural society. My goal is to bring together and advance concepts that cultivate emotional and social intelligence to complement the clinical skills required for the effective practice of medicine in the complex milieu of the 21st century.